6x+7=7x+6

Simple and best practice solution for 6x+7=7x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+7=7x+6 equation:


Simplifying
6x + 7 = 7x + 6

Reorder the terms:
7 + 6x = 7x + 6

Reorder the terms:
7 + 6x = 6 + 7x

Solving
7 + 6x = 6 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
7 + 6x + -7x = 6 + 7x + -7x

Combine like terms: 6x + -7x = -1x
7 + -1x = 6 + 7x + -7x

Combine like terms: 7x + -7x = 0
7 + -1x = 6 + 0
7 + -1x = 6

Add '-7' to each side of the equation.
7 + -7 + -1x = 6 + -7

Combine like terms: 7 + -7 = 0
0 + -1x = 6 + -7
-1x = 6 + -7

Combine like terms: 6 + -7 = -1
-1x = -1

Divide each side by '-1'.
x = 1

Simplifying
x = 1

See similar equations:

| 8x-52=2x+14 | | x^2-72x+256=0 | | 180=108(x+18) | | (12+8x)=1 | | (7+3i)-(2+3i)= | | 3y+3x-2=7 | | 1n+9n-10-3= | | 7(9x-3)=4(3x+2) | | 148-4x=60 | | (12-8x)=1 | | 4x-18+x^2-7x=10 | | 7(x+11)=18x+22 | | -2(d+4)-d-3=-3(d+5)+4 | | (5-i)(5+i)= | | -3.2(30)=-96 | | x^2-4x+1=k(x-4) | | x+2y+2z=-1 | | 3m-42-12+12=24 | | 3x+21=5 | | 7(n-8)-(6-n)= | | (3-i)+(1-2i)= | | 9x+12=15x-24 | | v/8=14 | | 95-7x=60 | | 5+5=10+10x | | 10(4-3i)= | | -3.2a=-96 | | 7y-168=3y | | 81r-48rt=0 | | 2a^2+11a=-5 | | w/12=9 | | 0.4(3x-15)=0 |

Equations solver categories